Recent advances in the flame retardancy role of graphene and its derivatives in epoxy resin materials. (October 2021) - Liu, Quanyi; Zhao, Yinlong; Gao, Shansong; Yang, Xiong; Fan, Rong; Zhi, Maoyong; Fu, Ming
Abstract: Epoxy resin has been widely used in aerospace, automotive construction and other fields due to its excellent mechanical performance, dielectric and corrosion resistance properties. However, epoxy resin can burn easily in the air and create the massive hazardous smoke and toxic gases during combustion, which may bring casualties and property losses, and limit its range of usage. It is therefore necessary to improve its flame retardant performance by using various flame retardants. Graphene and its derivatives have unique lamellar structure and can endow epoxy resin with good flame retardancy properties through the barrier effect of "tortuous path". In this wok, the recent research progress of graphene and its derivatives flame-retardant epoxy resin, and flame-retardant mechanism were systematically introduced. Moreover, the problems faced by flame-retardant epoxy resin and its development prospects have been analyzed. We hope that this review can provide valuable reference and inspiration for the researchers in this field.